Evaluation of The Implementation of Quality Management, Costs and Time in The Process of Self-Managed Project Development (Study on House Building Projects Muhammadiyah University Semarang Hospital) - M Martomo; Henny Pratiwi Adi; Kartono Wibowo (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
The construction of Universitas Muhammadiyah Semarang (Unimus) Hospital employs a self-management approach. During the construction phase, delays and a decline in building quality that did not align with the planning phase were observed. Therefore, a review of the management approach is necessary to ensure timely completion, maintained quality, and cost efficiency. This study evaluates the effectiveness of time, cost, and quality management in the construction project. The analysis method used is the interactive data analysis paradigm, involving data reduction, storage, and analysis using IBM SPSS 20. The analysis results indicate that time and cost management have been effective, with the construction work being completed within the set schedule and the costs not exceeding the Budget Plan. Quality management is rated very good with a score of 4.35, indicating that the construction process is strictly carried out according to specified materials and work procedures. Cost savings are also rated very good with a score of 3.89, indicating effective cost control. Time efficiency is rated good with a score of 4.06, showing that the project can run the schedule efficiently. Based on the research results, the researcher recommends enhancing leadership aspects and increasing active involvement of top management in supervision and strategic decision-making. This study also shows that self-management can promote transparency, efficiency, and high-quality outcomes in construction projects.